Modulation of mechanical and muscular load by footwear during catering - Kersting, UG; Janshen, L; Böhm, H; Morey-Klapsing, GM; Brüggemann, G-P (Ergonomics, 2005)
The BGN (Berufsgenossenschaft Nahrungsmithl und Gaststätten) reports 70% of job induced days off work to be connected with traumas of the ankle joint or overloading of the leg, knee and lower back, with an increased incidence in service areas outdoors (R. Grieshaber, personal communication). Workspace environments usually contain narrow passages, slopes or stairs and sudden changes between different surfaces. The aim of this study was to investigate the biomechanical load on the lower extremity and the low back during catering service when wearing different types of footwear. Thus, the potential for altering mechanical stress experienced during catering by variations in footwear was explored. Sixteen experienced waiters followed a course typical for a combined indoor - outdoor service area. Three different types of footwear were investigated using pressure distribution measurements, rearfoot goniometry and electromyography. A discriminant analysis revealed that the factors subject, shoe and surface affect rear foot movement or pressure distribution in different ways. A MANOVA demonstrated significant differences in loading parameters between footwear types. In general, these differences increased in magnitude in critical situations, such as climbing stairs or crossing slippery surfaces. The results of this study demonstrate that manipulations to footwear offer a great potential for modulating loads experienced during catering. Based on the results, the effects of constructional features are discussed. The method proposed can be applied to evaluate shoe modifications under realistic workplace conditions.